2018
DOI: 10.1063/1.5010340
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond laser scribing of CIGS thin film solar cell based on ITO bottom contact

Abstract: Cu(In,Ga)Se2 (CIGS) thin films, a promising photovoltaic architecture, have mainly relied on Molybdenum for the bottom contact. However, the opaque nature of Molybdenum (Mo) poses limitations in module level fabrication by laser scribing as a preferred method for interconnect. We examined the P1, P2, and P3 laser scribing processes on CIGS photovoltaic architecture on the indium tin oxide (ITO) bottom contact with a cost-effective nanosecond pulsed laser of 532 nm wavelength. Laser illuminated from the substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, we proceed with a fixed ITO film thickness of ∼200 nm as a harsh condition in a fundamental sense and also for the practical purpose of keeping material cost low. Although the current study is devoted to P2 laser scribing, the results can be effectively applied to the P3 laser scribing process as very similar scribing width and threshold were confirmed in the previous works by authors because laser-induced temperature and stress profiles are not affected much by the existence of an additional top contact (AZO; Al-doped zinc oxide) when a nanosecond laser beam of 532 nm wavelength is illuminated from the SLG substrate side …”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…However, we proceed with a fixed ITO film thickness of ∼200 nm as a harsh condition in a fundamental sense and also for the practical purpose of keeping material cost low. Although the current study is devoted to P2 laser scribing, the results can be effectively applied to the P3 laser scribing process as very similar scribing width and threshold were confirmed in the previous works by authors because laser-induced temperature and stress profiles are not affected much by the existence of an additional top contact (AZO; Al-doped zinc oxide) when a nanosecond laser beam of 532 nm wavelength is illuminated from the SLG substrate side …”
Section: Methodssupporting
confidence: 78%
“…Then, CIGS absorber layer of ∼2 μm thickness was first deposited on ITO by the coevaporator method, followed by deposition of CdS and i-ZnO (∼60 nm thick CdS by dip coating, ∼50 nm thick i-ZnO by sputtering). As authors previously reported, use of a thicker ITO film (∼400 nm) could efficiently suppress the ITO damage via a heat spreading effect during the P2 laser scribing process. However, we proceed with a fixed ITO film thickness of ∼200 nm as a harsh condition in a fundamental sense and also for the practical purpose of keeping material cost low.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…have reviewed the use of lasers for the manufacturing of chalcogenide PV thin film PV modules. [ 9 ] Lasers have become the technology of choice for the production thin film based PV modules including: CIGS [ 10,11 ] a‐Si, [ 12 ] and organic photovoltaics. [ 13 ] The combined advantages of very high process speed, reliability, precision, fine geometries, and the relative cleanliness of the process being the basis for the choice of lasers in automated production lines.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The history of the use of lasers in semiconductor thin film photovoltaics including scribing, film treatments, performance diagnostics, and thin film characterization from 1986 to 2010 was reviewed by Bartlome et al [8] Simonds et al have reviewed the use of lasers for the manufacturing of chalcogenide PV thin film PV modules. [9] Lasers have become the technology of choice for the production thin film based PV modules including: CIGS [10,11] a-Si, [12] and organic photovoltaics. [13] The combined advantages of very high process speed, reliability, precision, fine geometries, and the relative cleanliness of the process being the basis for the choice of lasers in automated production lines.…”
mentioning
confidence: 99%